Proverbs Translation Techniques in Anak Na Dangol Ni Andung, a Mandailing Folklore - Zainuddin Hasibuan; Nuraini Nuraini (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2022)
PurposeA text with many cultural terms was a complicated source text to translate into the target text because it contained different references as perceived by both language users. This research aimed to find out translation techniques applied by the translator in translating proverbs of Mandailing Folklore Anak Na Dangol Ni Andung into English and to explain its translation quality.MethodThis study made uses of a qualitative approach with a descriptive method. The data of the research were the text in Mandailingnese language as the source language and the English text as the target language; and were enriched by the key informants as the primary data. The data obtained were qualitatively analyzed using the theory of translation techniques.Results/FindingsThe research result showed that in translating proverbs there were four translation techniques namely single translation technique, couplet technique, triplet technique and quartet technique. It also showed that 45% of data were accurate and 55% translation were less accurate, 58,3% of data were acceptable and 41.7% translation was less acceptable, and 68.3% of data was high readable and 31.7% translation were medium readable.ConclusionFinally, the study concluded the quality of the translation products depended on the translation techniques by considering the accuracy, acceptability, and the readability of the target language.